Endoscopic Ultrasound–Guided Gastric Access to Facilitate Endoscopic Necrosectomy of a Large Walled-Off Necrosis in a Patient With Roux-en-Y Gastric Bypass Anatomy. (17th December 2021) - Tejedor-Tejada, Javier; Deshmukh, Ameya; Elmeligui, Ahmed; Parsa, Nasim; Dawod, Enad; Nieto, Jose
Abstract : Abstract :